Long-term interactive effects of N addition with P and K availability on N status of Sphagnum. (June 2018) - Chiwa, Masaaki; Sheppard, Lucy J.; Leith, Ian D.; Leeson, Sarah R.; Tang, Y. Sim; Neil Cape, J.
Abstract: Little information exists concerning the long-term interactive effect of nitrogen (N) addition with phosphorus (P) and potassium (K) on Sphagnum N status. This study was conducted as part of a long-term N manipulation on Whim bog in south Scotland to evaluate the long-term alleviation effects of phosphorus (P) and potassium (K) on N saturation of Sphagnum ( S. capillifolium ). On this ombrotrophic peatland, where ambient deposition was 8 kg N ha −1 yr −1, 56 kg N ha −1 yr −1 of either ammonium (NH4 +, Nred ) or nitrate (NO3 −, Nox ) with and without P and K, were added over 11 years. Nutrient concentrations of Sphagnum stem and capitulum, and pore water quality of the Sphagnum layer were assessed. The N-saturated Sphagnum caused by long-term (11 years) and high doses (56 kg N ha −1 yr −1 ) of reduced N was not completely ameliorated by P and K addition; N concentrations in Sphagnum capitula for Nred 56 PK were comparable with those for Nred 56, although N concentrations in Sphagnum stems for Nred 56 PK were lower than those for Nred 56. While dissolved inorganic nitrogen (DIN) concentrations in pore water for Nred 56 PK were not different from Nred 56, they were lower for Nox 56 PK than for Nox 56 whose stage of N saturation had not advanced compared to Nred 56. These results indicate that increasing P and K availability has only a limited amelioration effect on the N assimilation of Sphagnum at an advanced stage of N saturation. This study concluded that over the long-term P and K additions will not offset the N saturation of Sphagnum . Graphical abstract: Image 1 Highlights: Manipulation study evaluated P and K alleviation effects on N saturation of Sphagnum. NH4 + or NO3 − with and without P and K were added on the peatland over 11 years. Capitula N concentrations in Sphagnum for NH4 + were not reduced by adding P and K. DIN concentrations in pore water for NH4 + were also not reduced by adding P and K. Long-term P and K additions will not offset the N saturation of Sphagnum. Abstract : Over the long-term P and K additions will not offset the N saturation of Sphagnum.